2018
DOI: 10.1007/s00268-018-4590-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy May Not Influence the Remnant Liver Regenerations and Outcomes After Hepatectomy for Colorectal Liver Metastasis

Abstract: Preoperative chemotherapy may have no appreciable benefit for patients with CLM in terms of perioperative and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Furthermore, there was no significant difference in the frequency of repeat hepatectomy for recurrence due to insufficient regeneration of the remnant liver between patients with and without early recurrence. As the value of adjuvant chemotherapy after hepatectomy has yet to be established [25,26], the issue of resection feasibility in the event of early postoperative recurrence should be considered. Patients with CRC lymph node metastasis, synchronous liver metastasis, or multiple liver metastases require particularly careful surveillance in order to detect early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no significant difference in the frequency of repeat hepatectomy for recurrence due to insufficient regeneration of the remnant liver between patients with and without early recurrence. As the value of adjuvant chemotherapy after hepatectomy has yet to be established [25,26], the issue of resection feasibility in the event of early postoperative recurrence should be considered. Patients with CRC lymph node metastasis, synchronous liver metastasis, or multiple liver metastases require particularly careful surveillance in order to detect early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, surgical resection alone may offer little benefit, and chemotherapy is the main therapeutic strategy for advanced patients 52 . However, the clinical benefits of liver metastasis chemotherapy are not always obvious and multiple chemotherapy leads to an additional burden of patients due to adverse effects 52,53 . Therefore, the therapeutic response of patients with liver metastasis and timely control of the progression of liver metastases are of great significance to improve the survival and clinical benefits of patients with liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of preoperative chemotherapy on liver regeneration after liver resection is still controversial. Although some reports showed that preoperative chemotherapy itself does not affect liver regeneration and post-operative course (23)(24)(25), few studies have argued the adverse effects of chemotherapy-induced hepatotoxicity on early liver regeneration after liver resection. Current study suggested that splenic enlargement which represents liver injury caused by chemotherapy is related to impaired liver regeneration after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%